2005
DOI: 10.1007/s10979-005-2416-9
|View full text |Cite
|
Sign up to set email alerts
|

"I'd Know a False Confession if I Saw One": A Comparative Study of College Students and Police Investigators.

Abstract: In recent years, numerous high-profile DNA exonerations have surfaced, leading social science researchers, legal scholars, policy makers, and the news media to revisit the evidence upon which innocent people had been prosecuted, convicted, and imprisoned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
167
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 217 publications
(177 citation statements)
references
References 39 publications
9
167
1
Order By: Relevance
“…With specific regard to confessions, trained investigators also demonstrate poor accuracy and increased confidence. In the study which provided the methodology for obtaining true and false confessions for the present study, Kassin et al (2005) found that trained investigators were less accurate at identifying true and false confessions in comparison to untrained students, but they were more confident in their judgments. Trained investigators were not only overconfident in their abilities, but they also displayed a "guilt bias" which resulted in an increased perception of both true and false confessions as true.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…With specific regard to confessions, trained investigators also demonstrate poor accuracy and increased confidence. In the study which provided the methodology for obtaining true and false confessions for the present study, Kassin et al (2005) found that trained investigators were less accurate at identifying true and false confessions in comparison to untrained students, but they were more confident in their judgments. Trained investigators were not only overconfident in their abilities, but they also displayed a "guilt bias" which resulted in an increased perception of both true and false confessions as true.…”
Section: Discussionmentioning
confidence: 56%
“…Despite the fact that many professional investigators claim that their experience in interrogation enhanced their skill in detecting deception, Kassin, Norwick, & Meissner (2005) found that investigators with prior interrogation experience had poorer accuracy than students with no prior interrogation experience in identifying true and false confessions of criminal offenders. Further, there was no relationship between years of experience and accuracy.…”
Section: Deception Detection In Practicementioning
confidence: 85%
See 3 more Smart Citations